Prognostic value and usefulness of Pulmonary Artery Pulsatility index (PAPi) in evaluation of heart transplant candidates. (25th November 2020) - Bellettini, M; Pidello, S; Gallone, G; Frea, S; Masetti, M; Sabatino, M; Boschi, S; Giustetto, C; Boffini, M; Rinaldi, M; Potena, L; De Ferrari, G.M
Abstract: Background: Heart transplantation (HTx) is considered the best available treatment for patients with end stage heart failure. Candidate evaluation with right heart catheterization (RHC) is fundamental in order to exclude pulmonary hypertension with irreversible high pulmonary vascular resistance (PVR), which is associated with elevated post-HTx mortality. PVR, rather than directly measured, is derived by cardiac output and pulmonary artery pressures, which are strictly dependent on right ventricular (RV) function. The pulmonary artery pulsatility index (PAPi) is a hemodynamic parameter integrating the information of RV function and of pulmonary circulation, which could be useful in pre-HTx evaluation. Purpose: We designed this study to evaluate the potential predictive influence of pre-HTx PAPi on post-HTx survival and to assess whether this index could add useful information in the pre-HTx evaluation of patients with advanced heart failure. Methods: Consecutive adult HTx recipient at two medium-large tranplant centers between 2000 and 2017 with available data on pre-HTx RHC were retrospectively included. PAPi was calculated as the ratio of pulmonary artery pulse pressure to right atrial pressure. PAPi values in the lowest quartile were defined as reduced (PAPi<1.67). The primary endpoint was all-cause mortality at 1-year post-HTx. The association of reduced PAPi with the primary endpoint was evaluated. Cox regression was used to adjust for clinical and hemodynamic variables. Analyses stratified by PVR status (≥3 WU vs. <3 WU) were also performed. Results: Among 655 HTx recipients (female 20, 8%, age 53±11 years), median pre-HTx PAPi was 3.0 (interquartile range 1.67–5.32). Patients in the lowest versus the remaining PAPi quartiles had significantly reduced 1-year survival (78.0% vs 87.2%, p=0.006), also after adjusting for age, estimated glomerular filtration rate, total bilirubin, high PVR and urgent transplantation (adj-hazard ratio: 0.64; 95% confidence interval 0.51–0.82). When stratifying patients by estimated PVR status, reduced PAPi was associated with worse 1-year survival among patients with normal PVR (78.3% vs. 88.3% p=0.011), but not in those with increased PVR (78.0% vs. 82.6%, p=0.36) (Figure 1). Conclusions: Pre-HTx PAPi, integrating information of RV function and pulmonary circulation, provides incremental prognostic value over traditional clinical and hemodynamic parameters among HTx recipient. The prognostic value appears important among patients with normal estimated PVR, possibly due to an underestimation of PVR in patients with impaired RV function. The integration of PAPi in the pre-HTx evaluation may lead to better patient selection and post-HTx survival. Funding Acknowledgement: Type of funding source: None